Attenuated early pregnancy weight gain by prenatal lifestyle interventions does not prevent gestational diabetes in the LIFE-Moms consortium. (January 2021) - Redman, Leanne M.; Drews, Kimberly L.; Klein, Samuel; Horn, Linda Van; Wing, Rena R.; Pi-Sunyer, Xavier; Evans, Mary; Joshipura, Kaumudi; Arteaga, S. Sonia; Cahill, Alison G.; Clifton, Rebecca G.; Couch, Kimberly A.; et al.
Highlights: Lifestyle intervention is considered the first line strategy for prevention of GDM. Interventions initiated at 9–16 weeks gestation reduce GWG through to GDM diagnosis. Reduced rates of GWG produced no demonstrable effects on prevalence of GDM. GDM prevalence was not dependent on the use of diagnostic test methods. Factors related to poor glycemic control were already evident in the first trimester. Women 'at-risk' may be considered for first trimester screening of dysglycemia. Abstract: Aims: To examine the effect of lifestyle (diet and physical activity) interventions on the prevalence of GDM, considering the method of GDM ascertainment and its association with early pregnancy characteristics and maternal and neonatal outcomes in the LIFE-Moms consortium. Methods: LIFE-Moms evaluated the effects of lifestyle interventions to optimize gestational weight gain in 1148 pregnant women with BMI ≥ 25 kg/m 2 and without known diabetes at enrollment, compared with standard care. GDM was assessed between 24 and 31-weeks gestation by a 2-hour, 75-gram OGTT or by local clinical practice standards. Results: Lifestyle interventions initiated prior to 16 weeks reduced early excess GWG compared with standard care (0.35 ± 0.24 vs 0.43 ± 0.26 kg per week, p=<0.0001) but did not affect GDM diagnosis (11.1% vs 11.6%, p = 0.91). Using the 75-gram, 2-hour OGTT, 13. 0% of standard care and 11.0% of the intervention group had GDM by the IADPSG criteria (p = 0.45). The 'type of diagnostic test' did not change the result (p = 0.86). Women who developed GDM were significantly heavier, more likely to have obesity, and more likely to have dysglycemia at baseline. Conclusion: Moderate-to-high intensity lifestyle interventions grounded in behavior change theory initiated between 9 and 16-weeks gestation did not affect the prevalence of GDM despite reducing early GWG. Clinicaltrials.gov: NCT01545934, NCT01616147, NCT01771133, NCT01631747, NCT01768793, NCT01610752, NCT01812694.